Proglacial hydrology and drainage, southeastern Vestfold Hills, East Antarctica - Gore, Damian B.; Pickard, John (1998)
Three ice dams in southeastern Vestfold Hills, East Antarctica, dam a system of five lakes periodically, impounding more than ∼1.5 × 10 6 m 3 of water. Dam #a impounds 1.1 × 10 6 m 3 of water, while Dams #b and #c prevent the free drainage of the lake below Dam #a, and impound the remaining 0.4 × 10 6 m 3 . The mode of failure of these dams and the rate of impoundment release were not known until January 1993, when Dams #a and #b failed, allowing a flood to travel along a channel incised in sediment, and into Crooked Lake at >8 m 3 S -1 four times the peak midsummer discharge of the largest stream in Vestfold Hills. The flowpath from Lake #10 is determined by which of two dams fails first; the northwestern dam (#b) allows the impoundment to travel into Crooked Lake via Grimmia Gorge (observed during January 1993), and the northern dam (#c) into Crooked Lake via Sickle Lake, Lake Verkhneye and Foot Lake (observed during 1979 and 1990). Formation and failure of these Vestfold Hills ice dams is similar to 'snow dams' described from the Canadian Arctic. Floods released from the failure of the Vestfold dams provides an alternative explanation for a sudden increase in discharge at Ellis Rapids in January, 1976. Descriptions in this paper of glaciofluvial features are at odds with published notions that such features are absent from Vestfold Hills.